Current Status and Influencing Factors of Snakebite Diagnosis and Treatment Knowledge Among Medical Staff in China: A Cross-Sectional Study - Yanlan Hu; Chuanzhu Lv; Chuanzhu Lv; Chuanzhu Lv; Xingyue Song; Yong Gan; Juntao Wang; Juntao Wang; Wenjie Hao; Wenjie Hao; Lanfen He; Lanfen He; et al. (Frontiers Media S.A., 2023)
Objectives: This study aimed to determine the current status of the knowledge of diagnosis and treatment of snakebites among medical staff in China and its influencing factors.Methods: A cross-sectional survey of 12,581 medical staff was conducted in 12 provinces in China between June 2022 and February 2023. We analyzed the results using descriptive statistics, T-tests or analysis of variance, and a generalized linear model.Results: The average score of snakebite diagnosis and treatment knowledge among medical staff in China was 3.15 ± 2.15 out of a total score of 12. Through a generalized linear regression model, we found that gender, occupation, region, hospital level, work department, work tenure, training received in the diagnosis and treatment of snakebite, experience in snakebite diagnosis and treatment, availability of antivenom in the unit, and self-evaluation of snakebite treatment ability all affected the medical staff's scores of snakebite diagnosis and treatment knowledge.Conclusion: The knowledge level of snakebite diagnosis and treatment among Chinese medical staff is generally low, so it is imperative to conduct standardized snakebite diagnosis and treatment training for medical staff.